Aspergillus fumigatus antigen-reactive Th17 cells are enriched in bronchoalveolar lavage fluid in severe equine asthma - Wjst, Valentin F.; Lübke, Sabrina; Wagner, Bettina; Rhyner, Claudio; Jentsch, Maria-Christin; Arnold, Corinna; Lohmann, Katharina L.; Schnabel, Christiane L. (Frontiers in Immunology, 2024)
Introduction: Equine asthma (EA) is a common disease of adult horses with chronic respiratory pathology and common neutrophilic airway inflammation. It comprises hyperreactivity to hay dust components like molds and underlying dysregulated T cell responses have been suggested. Thus far, T cells have been analyzed in EA with conflicting results and antigen reactivity of T cells has not been demonstrated. Serological and epidemiological data point to the relevance of Aspergillus fumigatus as an antigen source in EA. Here, we aimed to identify and characterize Aspergillus antigen reactive T cells in EA. Methods: Cryopreserved bronchoalveolar lavage cells (BALC) and PBMC from healthy horses (HE, n=9), from those with mild-moderate (MEA, n=3), or severe asthma (SEA, n=8) were stimulated in vitro with the recombinant Aspergillus fumigatus antigens Asp f 1, or Asp f 7 combined with Asp f 8, to assess antigen reactivity, and with PMA and ionomycin (P/i) to assess overall T cell reactivity. Stimulated cells were analyzed by flow cytometry for CD4, CD8, IL-17, IL-4, and IFN-. Cytokine expression in all lymphocytes, and in CD4+ or CD8+ T cells was quantified and compared between the groups. In BAL fluid (BALF), soluble cytokines and chemokines were quantified by bead-based assays. Results: Antigen re-stimulation of BALC with Asp f 1 or Asp f 7/8 provoked higher frequencies of IL-17+ lymphocytes, CD4+IL-17+ Th17 cells, and CD4+IL-4+ Th2 cells in SEA compared to HE, while MEA and HE were similar. Antigen stimulation of PBMC did not result in group differences. P/i stimulation of BALC resulted in increased IL-17+ lymphocyte and CD4+IL-17+ Th17 cell frequencies in MEA compared to HE but the limited number of horses with MEA must be considered. P/i stimulated PBMC from MEA or SEA contained more IL-17+ lymphocytes compared to HE. Cytokines were hardly detected in BALF and similar between the groups, but CCL2 and CCL5 concentrations were increased in BALF from SEA or MEA, respectively, compared to HE. Conclusion: Horses with SEA have increased Aspergillus antigen reactive Th17 cells in their airways emphasizing local T cell responses to this mold which were quantified in EA for the first time here.